2015
DOI: 10.1097/psy.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and the Risk of Respiratory Problems in World Trade Center Responders

Abstract: These analyses provide further evidence that PTSD is a risk factor for respiratory symptoms and are consistent with evidence implicating physiological dysregulation associated with PTSD in the development of medical conditions. If these effects are verified experimentally, treatment of PTSD may prove helpful in managing physical and mental health of disaster responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 56 publications
(83 reference statements)
7
33
0
Order By: Relevance
“…Emotional lability might also be associated with LRS by heightened emotions straining sympathetic nervous system responses and in turn exacerbating respiratory symptoms. This is in line with evidence that psychiatric conditions such as PTSD are a risk factor for development of LRS [47].…”
Section: Personality Facets and Initial Health Consequences Of Traumasupporting
confidence: 76%
See 1 more Smart Citation
“…Emotional lability might also be associated with LRS by heightened emotions straining sympathetic nervous system responses and in turn exacerbating respiratory symptoms. This is in line with evidence that psychiatric conditions such as PTSD are a risk factor for development of LRS [47].…”
Section: Personality Facets and Initial Health Consequences Of Traumasupporting
confidence: 76%
“…These questions were derived from standard assessments used in previous studies of WTC responders that also validated the four-item composite [47]. Participants indicated whether or not they experienced each symptom.…”
Section: Methodsmentioning
confidence: 99%
“…In this cohort of WTC workers, PTSD has also been associated with self-reported incident lower respiratory symptoms during follow up (13). To our knowledge, however, this is the first report of an association between probable PTSD and either BDR or incident (new-onset) asthma.…”
Section: Discussionmentioning
confidence: 50%
“…Luft et al 16 studying police and non-traditional responders (clean-up workers, building trades, transportation workers, clergy and others) suggested that PTSD mediates the association between exposure and LRS. Kotov et al 18 analysed longitudinal data on these workers to demonstrate that PTSD increased the likelihood of LRS onset and decreased the rate of LRS remission.…”
Section: Introductionmentioning
confidence: 99%